Land Suitability Determination of NPP’s Potential Site in East Kalimantan Coastal Using GIS - Heni Susiati; I Gde Sukadana; Yarianto Sugeng Budi Susilo; Yuliastuti Yuliastuti (Jurnal Pengembangan Energi Nuklir, 2019)
Nuclear Power Plant (NPP) site selection is the key phase of the nuclear power plant process and significantly influence the construction cost and safety. In order to prepare for nuclear power programs in East Kalimantan province, Geographical Information System (GIS) analysis along the coast of East Kalimantan province, especially the Berau district, East Kutai, Kutai Kartanegara, Samarinda, Balikpapan, Penajam Paser Utara and the Paser. The research purpose is to find suitable site for nuclear power plants location using spatial analysis and modeling. The potential Nuclear Power Plant (NPP) site is based on several criteria, such as: geology, slope, soil type, land use, hydrology, and existing road network. Based on the weighting and ranking results using GIS application: there are three locations serve as the potential NPP sites are obtained Kutai Kartanegara and Kutai Timur regency. Next, land suitability analysis is done by using GIS application which shows potential sites suitable general and specific criteria of the site evaluation process development.